Livelihood Strategy of Coastal Community: A Case Study in Tanjung Saleh Islands, Kubu Raya District, Indonesia - Sudrajat, Jajat (Universitas Negeri Semarang, 2016)
This study is intended to identify the characteristic of livelihood strategy and to formulate the exit strategy from poverty trap in a coastal community. This study was done in Tanjung Saleh islands, one from 39 islands at Kubu Raya District, West Kalimantan Province, Indonesia. Data were collected by depth interviews, group interviews, observation, and literature study. The results of this study show that the livelihood strategies at Tanjung Saleh islands can be identified into five types: (a) the strategy that relied on the natural resources extraction, (b) traditional agriculture cultivation strategy, (c) household worker utilization strategy, (d) migration strategy, and (e) institutional strategy. The institutional strategy is categorized as exit strategy from poverty trap meanwhile the other strategies are categorized as survival strategy. Fact in the field shows that institutional strategy and the role of women are important factor to support the fishermen household livelihood system. There are two institutions often utilized in fishermen community, “arisan” (rotational saving and credit association) custom and patron client relationships between fishermen and village traders. Through the utilizing of social capital on both institutions, the fishermen household can access financial capital effectively. Therefore, the nurturing of social capital and the role of women must be considered in arrangement of sustainable livelihood strategies in fishermen community.